(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article analyzes the essence and stages of formation of the modern world economy in the context of digital and green transformation. The main goal of the study is to determine the impact of digital and green factors on the level of economic development of countries and their participation in the world economy. Theoretical-analytical and comparative approaches were used in the research process. The stages of formation of the world economy were studied based on the periods of industrialization, globalization and modern transformation. The impact of the digital economy and the green economy on economic growth was also analyzed. The results showed that digital technologies and green development factors are becoming the main drivers of modern economic growth. In particular, the harmonious development of these two areas is of great importance in increasing the competitiveness of countries in the global economic system. In conclusion, it can be noted that the future development of the modern world economy depends on the integration of digital innovations and the principles of sustainable development, and countries that can effectively implement these areas will have an economic advantage.